Precision Agriculture in Brazil: current situation, challenges and perspectives (Research, Society and Development, 2020)
Ensuring food security for future generations has been a recurring challenge in the face of population growth. Therefore, several technological innovations have contributed to the efficient management of agricultural production to ensure productivity and sustainability. In this scenario, Precision Agriculture stands out, a set of techniques to manage the differentiated application of inputs, considering spatial and temporal variability, increasing production yield, and reducing environmental impact. In view of this, this work aimed to provide a diagnosis of the current situation of Precision Agriculture in Brazil, identifying the challenges and development prospects. This is a basic, qualitative, and exploratory research, in which bibliographic and documentary research structured under the following aspects were used as procedures: legal framework, performance of the government and main entities, technological production and adoption. Analyzing the defined aspects, it is concluded that there is a joint commitment of private companies, research centers, universities, and associations to spread the practices of agricultural precision; however, there is some resistance from the producers. There was also a need for the development of technologies to make the country competitive and the collection of data specified for an accurate diagnosis of the sector.